2019
DOI: 10.1111/jan.14267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ABCDE bundle on the prevention of post‐intensive care syndrome: A retrospective study

Abstract: AimTo identify the effects of each domain of the early and modified ABCDE bundle on post‐intensive care syndrome (PICS).DesignThis is a retrospective study.MethodsWe analysed the data from electronic medical records of 91 intensive care patients who received therapeutic interventions in stages, based on the early ABCDE bundle (admitted to the intensive care unit [ICU] from June – August 2013) and 94 patients who received interventions using a modified ABCDE bundle developed through continuous quality improveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(52 citation statements)
references
References 42 publications
2
44
1
5
Order By: Relevance
“…To this end, it may be effective to use the ABCDE bundle (Morandi et al, 2011;Vasilevskis et al, 2010) to routinely stimulate patient arousal, monitor delirium while controlling pain, and perform early mobilization. Using this bundle has been shown to increase the number of days where an individual does not experience delirium or being in a coma (Bounds et al, 2016;Hirshkowitz, 2004), and leads to PICS prevention (Lee et al, 2020). This can contribute to protecting 'factual memory' and fostering positive memories among patients.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, it may be effective to use the ABCDE bundle (Morandi et al, 2011;Vasilevskis et al, 2010) to routinely stimulate patient arousal, monitor delirium while controlling pain, and perform early mobilization. Using this bundle has been shown to increase the number of days where an individual does not experience delirium or being in a coma (Bounds et al, 2016;Hirshkowitz, 2004), and leads to PICS prevention (Lee et al, 2020). This can contribute to protecting 'factual memory' and fostering positive memories among patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Early Psychologic Intervention (Peris et al., 2011 ) has been shown to cut the prevalence of anxiety, depression and PTSD by half. Another programme that included a complex, preventive psychological intervention (Lee et al., 2020 ) found self‐reported PTSD symptom severity did not fall at six months. Some reports have shown a favourable impact of the ICU diary in patients and families (Garrouste‐Orgeas et al., 2012 ; Knowles & Tarrier, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review (Schofield‐Robinson et al., 2018 ) of follow‐up services found it was unclear whether they reduced depression, cognitive or physical function, or increased work and educational attendance. The ABCDE bundle on the prevention of PICS (Lee et al., 2020 ) reduced deep sedation and immobilization. A Spanish trial found that a visit before hospital admission did not influence anxiety or depression (González‐Martín et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical ventilation (MV) is a necessary and critical part of life-supportive therapy for patients in the intensive care unit (ICU) but is associated with significant morbidity and mortality, related to both harm from MV itself (i.e., ventilator-induced lung injury) and the infectious, psychiatric, and neuromuscular sequelae of intubation, sedation, and immobility ( 1 3 ). How we manage patients on MV has significant and direct impacts on patient outcomes as well as hospital costs ( 4 6 ).…”
mentioning
confidence: 99%
“…This is probably most clearly demonstrated in acute respiratory distress syndrome (ARDS), for which the use of lower tidal volume, pressure-limited strategies has consistently been shown to reduce patient mortality ( 5 , 7 , 8 ). Similarly, significant evidence exists supporting other best practices, including the use of lower tidal volume strategies for patients without ARDS ( 9 11 ), the early use of prone positioning for patients with moderate/severe ARDS ( 12 ), protocolized extubation protocols ( 13 ), and implementation of the ABCDEF bundle (assess, prevent, and manage pain; both spontaneous awakening trials and spontaneous breathing trials; choice of analgesia and sedation; delirium assessment, prevention, and management; early mobility and exercise; and family engagement and empowerment) ( 3 , 14 , 15 ), aimed at decreasing ventilator-associated pneumonia (VAP) and neuromuscular weakness.…”
mentioning
confidence: 99%